Eksplorasi Gaya Kepemimpinan dalam Mewujudkan Kepuasan Kerja dan Loyalitas Anggota Keluarga Pabrik Kata-Kata Joger - Santana, I Putu Gede Adi; Supriyadinata Gorda, A.A.Ngurah Eddy (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
This study delves into the exploration of leadership styles in fostering job satisfaction and loyalty among the members of the Joger Word Factory family, utilizing a qualitative descriptive approach. Data were collected through documentation, observation, and in-depth interviews with 7 informants. Data analysis was carried out using a triangulation approach, encompassing both sources and techniques, guided by the theory of Miles et al. The findings reveal that a democratic leadership style has been adopted by the Joger company. A well-implemented leadership style is evidenced by Mr. Joger's decision-making ability, motivational skills, effective communication, adeptness in supervising subordinates, responsible, and emotional control. Furthermore, the job satisfaction of each member of the Joger family can be enhanced through several components such as salary, promotions, supervision, and relationships with colleagues. The study demonstrates that the application of a good leadership style can elevate job satisfaction, which then increased loyalty. This is reflected through employee attitudes, including adherence to rules, responsible, willingness to collaborate, a sense of belonging, interpersonal relationships, and a positive attitude toward work. This research offers a positive contribution to the literature on human resource management and provides practical insights for the Joger company in enhancing employee satisfaction and loyalty